1996
DOI: 10.1108/02652329610151331
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation modelling of overall satisfaction and full use of services for ATMs

Abstract: Tests an hypothesized model which measures the overall satisfaction gained from, and the full spectrum of services attached to, the use of automated teller machines (ATMs). Sees overall satisfaction as the end result of a combined number of antecedents. Uses a LISREL model to test the structural effects of a number of exogenous variables (i.e. expectations and perceived risk) on a number of latent variables (desires congruency, self‐congruity, perceptions of relative influence and behavioural intentions) to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Using service quality as the antecedent to satisfaction is more logical and that why it has been taken into consideration. This is because satisfaction is an important goal to be achieved by bank marketers and if the banks want to increase satisfaction, they can do it through service quality (Goode et al, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using service quality as the antecedent to satisfaction is more logical and that why it has been taken into consideration. This is because satisfaction is an important goal to be achieved by bank marketers and if the banks want to increase satisfaction, they can do it through service quality (Goode et al, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fornell (1992) demonstrated that there is a positive correlation between customer satisfaction and positive word-of-mouth; in other words, satisfied consumers are more inclined to express a preference for a service provider and recommend that provider to others. Other authors (Parasuraman et al, 1988;Goode et al, 1996;Zeithaml et al, 1996) have confirmed that a significant positive relationship exists between perceptions of superior service quality and consumer recommendation to other potential customers.…”
Section: Consumer Behaviour and Sst Banking Servicesmentioning
confidence: 87%
“…Second, it has been shown that satisfied consumers have a greater predisposition to positive word-of-mouth (Fornell, 1992), as do users of ATMs (Goode et al, 1996) and internet banking (Mols, 1998). The following hypothesis is therefore proposed:…”
Section: Hypothesesmentioning
confidence: 99%
“…Hence, it is argued, service quality is an important factor in deciding the success of a service firm to act upon the customer’s intention to travel to their destination. As satisfaction, which reflects the post-purchase evaluation of products or services given the expectations before the purchase is dependent on the ability of the supplier to meet the customer’s expectations (Fornell, 1992; Oliva et al , 1992), the current research used service quality as the antecedent to satisfaction, which seems to be more logical because satisfaction is an important goal to be achieved by the marketers to increase the customer’s intention to purchase (Goode et al , 1996). For example: a research conducted by Bitner (1990) on 145 tourists in an international airport reflects that satisfaction is the antecedent to service quality.…”
Section: Literature Review and Development Of Conceptual Frameworkmentioning
confidence: 99%